2016
DOI: 10.1523/jneurosci.3643-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Organization of the Neuronal Circuits of the Claustrum

Abstract: The claustrum, a poorly understood subcortical structure located between the cortex and the striatum, forms widespread connections with almost all cortical areas, but the cellular organization of claustral circuits remains largely unknown. Based primarily on anatomical data, it has been proposed that the claustrum integrates activity across sensory modalities. However, the extent to which the synaptic organization of claustral circuits supports this integration is unclear. Here, we used paired whole-cell recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
112
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(145 citation statements)
references
References 67 publications
26
112
1
Order By: Relevance
“…PV− and PV+ aspiny neurons also exhibited multiple fast inward PSCs beyond E Cl − (Figure S5B). These lines of evidence suggest that the ACC recruits excitatory and inhibitory claustral microcircuits, which elaborates upon previous work (Kim et al, 2016). …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…PV− and PV+ aspiny neurons also exhibited multiple fast inward PSCs beyond E Cl − (Figure S5B). These lines of evidence suggest that the ACC recruits excitatory and inhibitory claustral microcircuits, which elaborates upon previous work (Kim et al, 2016). …”
Section: Resultssupporting
confidence: 89%
“…Our data demonstrate that ACC monosynaptically drives claustrum microcircuitry consisting of spiny projection neurons that target cortex, PV− interneurons, and PV+ interneurons. These findings confirm and elaborate upon previous work (Kim et al, 2016). In addition, we found that claustrum amplifies 1- to 10-Hz ACC input persistently but 20-Hz ACC input only transiently and that claustrum inhibitory microcircuits critically constrain this amplification.…”
Section: Discussionsupporting
confidence: 93%
“…Although claustrum projection neurons are glutamatergic (Brand 1981; Braak and Braak 1982; Hur and Zaborszky 2005; Watakabe et al 2014; Kim et al 2016), the downstream impact of claustrum activity on cortical layers in rodents is unclear. As such, we injected AAV-ChR2 into claustrum (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent electrophysiological observations demonstrate a laminar structure of the claustrum (Orman, ), with the conclusion that the claustrum has strong excitatory connections organized along its rostrocaudal axis, with little connectivity between claustral excitatory neurons along the dorsoventral axis. A recent detailed patch‐clamp study of connectivity in the claustrum in coronal sections of the mouse brain described prevalent inhibitory connectivity of PV neurons onto claustral neurons, and prevalent feed‐forward inhibition driven by cortical inputs to the claustrum (Kim et al, ). Virtually no connections were observed between excitatory claustral neurons in this study, potentially consistent with the observation of Orman (), as these connections were investigated in coronal slices, potentially destroying lateral connectivity in the claustrum.…”
Section: Discussionmentioning
confidence: 99%